Calving rates, long-range movements and site fidelity of southern right whales (Eubalaena australis) in south-eastern Australia - Watson, Mandy; Stamation, Kasey; Charlton, Claire (J. Cetacean Res. Manage., 2021)
Within New Zealand and eastern Australia, over 58,000 southern right whales were harvested by commercial whalers between 1790 and 1980, with approximately 19,000 harvested from south-eastern Australia. Local extirpation is believed to have led to a loss of cultural memory of calving areas, contributing to the limited recovery of the south-eastern Australian population. While the number of whales observed using the south-eastern Australian coastline is increasing, there has been no change over three decades in the annual abundance of cow-calf pairs at Logans Beach in Warrnambool, Victoria, the only established calving ground in the region. Knowledge of life history parameters of the south-eastern Australian population is lacking. Here, we examine sightings and photo-identification data from southern Australia to investigate calving intervals, long range movements and fidelity to the Logans Beach nursery ground. Sightings data revealed at least 93 calves were born at Logans Beach between 1980 and 2018 (an average of 2.6 per year) with a mean calving interval of 3.5 Â± 1.0 years (Â± SE, n = 34). Comparison between photo-identification catalogues compiled for south-eastern and south-western Australian populations shows that southern right whales are wide ranging within southern Australian waters. Females can be sighted at locations as far apart as 3,800 km across seasons and there is overlap in the wintering range of the south-eastern and south-western populations, with at least 7% of whales using both regions. We also provide the first report of an Australian southern right whale female with strong site fidelity to a calving area in one region relocating long-term to a calving area in another region. This work highlights several knowledge gaps, such as; the location of feeding and conception grounds for this population as well as the degree of mixing between the two Australian populations outside their wintering areas. In addition, the proportion of female calves born at Logans Beach returning to their natal site to calve remains unclear. Our work provides the first assessment of calving rates, movement and site fidelity within the south-eastern Australian population, critical for understanding constraints to recovery and informing conservation management of southern right whales in Australia. Targeted, long-term monitoring programs across the south-eastern Australian region are needed to provide demographic information on which to base predictions of the impacts of anthropogenic threats such as noise disturbance, entanglement and vessel strike.